Mentoring Adolescent Girls as a Strategy for Anemia Prevention - Kiswati, Kiswati; Umami, Riza (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2026)
Anemia among adolescent girls remains a significant public health problem both globally and nationally. The high prevalence is mainly caused by increased iron requirements during growth and menstruation, as well as low knowledge and adherence to iron supplementation. This community service program aimed to improve knowledge and hemoglobin (Hb) levels among adolescent girls through health education and iron supplementation. The methods included hemoglobin level screening, health education using video and leaflet media, and weekly iron tablet supplementation for two months with regular monitoring. The participants were 50 adolescent girls from Mitra Junior High School, Jember Regency. The results showed a significant improvement in knowledge, with the proportion of good knowledge increasing from 0% to 16%, and poor knowledge decreasing from 66% to 6%. In addition, hemoglobin levels improved, with normal Hb increasing from 40% to 64%, and anemia prevalence decreasing from 60% to 36%. In conclusion, the combination of education and iron supplementation is effective in improving knowledge and hemoglobin status among adolescent girls. However, further efforts are needed, including adherence monitoring, continuous nutrition education, and multisectoral involvement to optimize anemia prevention programs.